Analisis Perbandingan Kinerja Keuangan PT. Ace Hardware Indonesia Tbk Sebelum dan Sesudah Pandemi Covid-19 - Khairudin, Khairudin; Grysia, Fansisca (CV. Lafadz Jaya, 2022)
The main focus of this research is to be able to measure and make a comparison of a company's financial performance before the pandemic and also after the covid-19 pandemic at PT. Ace Hardware Indonesia Tbk. The population is also the sample used for this research, namely using the financial statements at PT. Ace Hardware Indonesia Tbk. in 2019 and 2020. The method used for this research is descriptive quantitative. This time the measurement uses only three ratios, namely the liquidity ratio, solvency ratio, and also the profitability ratio. The results that have been studied show that there are differences in the financial performance of PT. Ace Hardware Indonesia Tbk before and after the covid-19 pandemic. There are several indicators that have decreased, namely the profitability ratio, ROA has decreased due to declining sales after the covid-19 pandemic. The company's burden increased due to the covid-19 pandemic which caused a decrease in NPM but was still within reasonable limits. However, there was a positive impact after the covid-19 pandemic, namely on the liquidity ratio, where the current ratio or current ratio increased after the covid-19 pandemic, which means the company's financial situation is getting better in paying its debts. The very current ratio and after the covid-19 pandemic was stated to be still in the good category, but the company was considered inefficient in utilizing its assets after the entry of the covid-19 pandemic. After the covid-19 pandemic, the DER value decreased, indicating that the debt and liabilities in the company were smaller than all the assets owned by the company. The company experienced a decrease in DAR meaning that the company could minimize its debt and maximize its asset management.